Residual Silica in Raw Jute and Elimination Scope (Global Journal of Science Frontier Research, 2019)
Jute- the golden fibre of Bangladesh is used widely for various purposes But it is reported that there is a draw back facing in the industrial machinery while processing the jute fibre for its product due to the presence of Residual Silica Silicates Under very warm condition the silicates may split into silica Since silica and silicates are semi -metal they exhibit conductive property in raw jute and also in jute products An investigation was carried out in BJRI PDB Ghorasal Laboratory to find out the content of Residual silica silicates by Spectrophotometric and Ashing methods in retted raw jute fiber of Faridpur zone for suggesting the remedial measure